Faktor-faktor risiko karsinoma esofagus di hospital Kuala Lumpur - Bangrose S.,; Kasuadi H.,; Lee G.K.,; Marlizan M.Y.,; Md. Nazeri N.,; Md. Sharifudin S.,; Norliza M.,; Ronald A.D.,; W.M. Azan., (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1994)
A case control study was done to determine the distribution of esophagus carcinoma according to age, sex, ethnic group and to determine the risk factor of esophagus carcinoma following alcohol intake, smoking and corosive ingestion. Thirty -two cases and control were selected from surgical wards at Kuala Lumpur Hospital (HKL) from January to September 1993. Patients data were collected from HKL and UKM surgical wards, and was matched with sex, age and ethnic group. Majority of esophagus carcinoma patient was Chinese (43.75%), India (28.13%) and Malay (28.13%). Fifty percent of cases were male. There are significant relationship between esaphagus carcinoma and alcohol intake (p<0.05) and corrosive ingestion. Alcohol intake is the major risk factor with the ods ratio of 3.8 [95% confidence limits (1.10, 13.86). Smocking is also an important risk factor with the ods ratio 3.57% (95% CL: 1.07, 12.32].